Pengoptimalan Kecerdasan Spiritual Melalui Praktik Rukun Islam dan Rukun Iman: Perspektif Al-Quran dan Hadits - Sari, Rahma; Sutrisno, Sutrisno (Nusantara: Jurnal Pendidikan Indonesia, 2024)
Purpose – This study aims to explore spiritual intelligence and the methods to optimize the spiritual intelligence of early childhood based on the teachings of the Al-Qur’an and Hadith.Method – The research method employed in this study is a literature review, which involves the examination of theories, writings, works, and images as reference sources. The researchers utilized various sources and gathered data from article references, journals, textbooks, and literature reviews concerning spiritual intelligence in early childhood. This collected data was then meticulously examined and analyzed using the researchers' own words and interpretations.Findings – The results indicated that optimizing spiritual intelligence in children can be achieved by interpreting the pillars of faith and the pillars of Islam in ways that are relatable and understandable to the child. This process involves connecting these religious principles to everyday experiences and contexts that are familiar to children, thereby making the concepts more accessible and meaningful. The approach is firmly grounded in the teachings and the inherent perfection of the Qur’an and Hadith, ensuring that the methods used are both authentic and spiritually enriching for early childhood development. Research Implications – This research provides a significant contribution for researchers and readers by enhancing their understanding of spiritual intelligence and offering practical insights into how to optimize spiritual intelligence in children. By exploring methods based on the teachings of the Qur’an and Hadith, this study offers valuable guidance for effectively fostering spiritual growth and development in early childhood.